About the Catholic Kings´ North African policy: The principalities of Badis, Xauen and Tetuan (1491-1515) - López de Coca Castañer, José Enrique (En la España Medieval, 2018)
This paper studies political dealings between postconquest Granada and the Moroccan principalities of Badis, Xauen and Tetouan. Although all of them were in the territory reserved for a future Portuguese conquest, they were seen as a menace by the Spanish authorities because their piratical activities. Following Crown´s orders, the secretary Hernando de Zafra, the Count of Tendilla and other officials were commisioned to solve that menace in diferent ways.
Keywords: Granada; Morocco; Badis; Chauen; Tétouan; Political Dealings; Catholic Kings.